Identification of Mine Water Source Based on AHP-Entropy and Set Pair Analysis - Xianming Zhao; Zhimin Xu; Yajun Sun (Geofluids)
After a water inrush disaster occurs in the mine production process, it is urgent to identify the source of water inrush and formulate corresponding countermeasures in the complex hydrogeological condition of coal mines. Therefore, accurate identification of mine groundwater source is one of the keys to prevent mine water disasters. According to the difference between the hydrochemical compositions of three aquifers in Chengjiao coal mine, six primary ions (Na++K+, Ca2+, Mg2+, SO42-, Cl,- and HCO3-) were selected as the indexes for groundwater source identification. On this basis, a mathematical model for groundwater source identification was established by combining the analytic hierarchy process- (AHP-) entropy weight method and the set pair analysis (SPA) theory. Next, this model was used to identify the sources of 10 sets of water samples from the mine, and then, the identification results were compared with the results of conventional models established using Fisher discriminant analysis (FDA) and Bayes discriminant analysis (BDA) methods. The results show that the SPA-based model performs better in identifying the groundwater sources. Furthermore, the model was used to identify the source of water inflow in the No. 21304 panel. The analysis on identification results reveals that the area close to the F20 normal fault tends to receive water supply from the Ordovician limestone aquifer and the Taiyuan Formation limestone aquifer, so it should be regarded as a key area for water inrush prevention and control.